The Art of Dwelling in the “Peculiar Nook of the Earth”: Revisiting The Ruined Cottage - 유선무 (비평과이론, 2018)
This essay is an attempt to read The Ruined Cottage as a sustained reflection on the ethos of “ecstatic dwelling,” a rethinking of oikos in the face of “the elemental, the uninhabitable, and the incomprehensible.” While critics view the so-called “reconciling addendum” in The Ruined Cottage as the facile idealization of unity between nature and human imagination, this essay claims that it is the very idealization that the “addendum” criticizes. Instead of translating nature’s response to human suffering into human terms, the Pedlar presents the spear-grass, a weed, as a model for “ecstatic dwelling,” which can be learned only when one radically transforms traditional discourses of humanism, personhood, and community. Margaret’s failure to dwell and the subsequent destruction and ruination of the dwelling are intermeshed with her melancholic commitment to the notion of oikos as an original, stable site of unity and identity. In contrast, the spear-grass in the “addendum” practices the art of dwelling that makes a home in exile. The survival of the spear-grass in the ruined cottage correlates with a particular sense of belonging, which does not have an antithetical relationship to non-belonging. Unloved and unwanted in the world and never given a proper place, as in the case of Margaret, the spear-grass experiences a foreign place as a home, one that is redefined as a place of difference, where one can enjoy tranquility, however, precarious and temporary.
Keywords: Ecstatic dwelling; The Ruined Cottage; oikos; ecology; belonging; 황홀한 거주함; 거주지; 허물어진 오두막; 오이코스; 생태학